Solid Particle Erosion Models and their Application to Predict Wear in Pelton Turbine Injector - Bajracharya, Tri Ratna; Shrestha, Rajendra; Timilsina, Ashesh Babu (Journal of the Institute of Engineering, 2020)
Analysis of water quality of Himalayan originated rivers reveals the heavy sediment loading with a major portion of the sediment being hard mineral, quartz. Despite the incorporation of desanders to reduce the sediment content passing through hydro mechanical parts, significant wear is being reported in south-Asian hydroelectric projects. Repeated impact of such solid particles which are harder than the material of mechanical parts (mostly steel) is known to cause the erosion. Flow parameters, impact angle, mechanical properties of wall and particle, particle shape and size are commonly explored variables that affect the erosion of solid by the sediment-laden flow. In order to predict such erosion, starting with Finnie erosion model, several other erosion models considering aforementioned variables are proposed but are mostly case dependent. Application of numerical methods to understand flow problems constitutes the field of Computational Fluid Dynamics (CFD). Due to enclosed flow, reactions turbines took accelerated development in the investigations by CFD modeling. However, free surface jet and complex flow mechanism in buckets have been a major barrier to the application of CFD in case of Pelton turbines. Recent advancements in computational techniques, technological advancements have enabled to investigate flow in Pelton turbine by CFD. However, it is least understood which among the proposed erosion models will predict erosion occurring in Pelton turbine and assembly. This article explores about erosion in Pelton turbine, various erosion models and state of the art in modeling erosion of Pelton turbine injector. It is discussed which among the erosion models shall best predict the erosion occurring in the Pelton turbine injector. A short list of erosion models is then given which can be applied for the case of erosion in Pelton turbine injectors.